Il teatro come metafisica del concreto secondo Artaud - Cocito, Sara (Filosofia, 2023)
This paper discusses Antonin Artaud’s conception of the relationship between thought and existence, affirming that rational thought never manages to grasp concrete existence. Through the revolution of theatre, though, Artaud pursues a new form of thought capable of preserving its intimate connection with life. Therefore, he questions traditional Western theatre, which relies on representation, mimesis and on the supremacy of text, of language, of the written word. In contrast, he proposes a new idea of theatre, with an emphasis on gestures, movements, and symbols. According to Artaud, this form of theatre, deeply rooted in the materiality of the staging, becomes a metaphysical practice which allows to break the barriers between the abstract and the concrete and to draw ideas belonging to a spiritual order, revealing hidden truths about human existence.